INVESTIGATION OF REASONS OF BRASS COATING SEPARATION AT COILING OF WIRE - E. S. Seregina (Литьë и металлургия)
The reasons of brass coating separation at coiling of wire are investigated. It is shown that constant perfection of the investigation methods is one of the ways of achievement of high level quality of the production of RUP “BMZ”